ChemInform Abstract: Screening of N, N‐Bidentate and N, N, N‐Tridentate Pyridine‐Based Ligands in the Catalytic Allylic Oxidation of Cyclic Olefins. Issue 15 (April 2015) - Solinas, Maurizio; Sechi, Barbara; Chelucci, Giorgio
Abstract The shown iminopyridine catalyst (CAM) gives the best results in the title reaction and enantioselectivities up to 53% are obtained.